Education, skill, and wage inequality: the situation in California. - Jacoby, Sanford M.; Goldschmidt, Pete (Challenge (05775132))
A study was conducted to examine employment and skill trends and the reasons for the recent increase in wage inequality in California. Data from the occupational projections prepared by California's Employment Development Department for the periods 1990-2005 and 1993-2005 were compared to identify recent trends in occupational growth in the fifty occupations that make the largest contribution to absolute employment growth. The results indicate that although the middle tier of occupations—those requiring skills consistent with a high school diploma—is not expected to grow very rapidly over the next ten years, rapid growth is expected in both highly skilled occupations paying high wages and unskilled occupations paying relatively low wages. As a result of this bimodal distribution, the average pay and skill levels of the fastest-growing occupations in California are slightly less than those of the entire stock of occupations. As the current trend is toward faster growth in the top third of the skill structure, wage inequality may endure even as wages increase.